The Influence of Social Media Marketing on Instagram to the Creation of Brand Equity: Case of @kitabisacom - Agusta, Monica Trixie; Widiasari, Natalia (Jurnal Ilmu Komunikasi, 2025)
A social enterprise initiated a crowdfunding application to gather funds from people. Those who are in need could post an announcement of the amount of funds they needed. Majority used the funds for medical treatment, some used to rebuild infrastructure in places that experienced calamities. The platform’s popularity not only gets good attention but also invites those who had scamming intentions. Thus, continuous communication and dialogue must be in place to restore trust. This study investigates the influence of social media marketing that is conducted by the organization via social media account kitabisacom on Instagram to the creation of brand equity. The independent variable is social media marketing that consists of four dimensions which are brand awareness, brand loyalty, brand association and perceive quality. Data is gathered using purposive sampling. The finding revealed that kitabisacom is a top-of-mind platform related to digital donation and has a positive sentiment among the crowds.